Pengaruh Penggunaan Model Pembelajaran Generatif Berbantuan Simulasi PhET Untuk Meningkatkan Pemahaman Konsep Peserta Didik - Abdul Quddus; Gunawan Gunawan; Sutrio Sutrio; Ni Nyoman Sri Putu Verawati (Indonesian Journal of Applied Science and Technology, 2024)
This study aims to evaluate the effectiveness and influence of a PhET-assisted generative learning model on improving students' understanding of physics concepts. This research employed a quantitative approach utilizing a one-group pretest-posttest design. Data were collected using a concept understanding test and analyzed using the Normalized Gain (N-Gain) score to determine effectiveness, as well as a paired sample t-test to assess statistical significance. The results yielded an N-Gain value of 0.40, categorizing the improvement as moderate. Furthermore, the t-test analysis revealed a significance value of 0.000 (p < 0.05), leading to the acceptance of the alternative hypothesis. Consequently, it can be concluded that while the PhET-assisted generative learning model significantly influences students' concept understanding, its implementation is currently classified as less effective, suggesting the need for further optimization.